(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion, 2015)
The aim of this paper is to explore the impact of organizational culture on the process of organizational learning and knowledge management. This goal has been achieved through reviewing the relevant literature and synthesizing the conclusions found in it. The review of the researches has shown that organizational culture positively impacts and stimulates organizational learning in the degree in which its assumptions, values, and norms are consistent with the activities taken to create and use organizational knowledge. The review of the research has also shown that in order to have a positive impact on organizational learning and knowledge management, organizational culture must contain certain assumptions, values, and norms concerning four issues: individual development; changes; interactions, cooperation and communications; and environment. This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.